PENGEMBANGAN SISTEM INFORMASI PENGELOLAAN DATA FAKTUR PENJUALAN DAN PIUTANG MENGGUNAKAN METODE PROTOTYPE PADA PT.SIPORENNU MAKASSAR - The Lavenia Thesman; Abdullah (KHARISMA Tech, 2018)
The aim of the research is to design and build a information system of data management of sales invoice and receivables at PT.SIPORENNU using Prototype Method. This research is divided into five stages: Communication, Quick Modeling, Construction, Deployment. The application will be developed using Visual Basic 6.0 which is the part of Visual Studio 2008 for the desktop based application.